2018
DOI: 10.3329/akmmcj.v9i2.39210
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width (RDW) and Hb% in the Detection of Iron Deficiency Anemia in Pregnant Women

Abstract: Background: Detection of iron deficiency early during pregnancy is essential for correct management. Red cell distribution width (RDW) is a new routine parameter in fully automated hematology analyzer that can give the idea of early iron deficiency before Hb%. This study was aimed to see the role of red cell distribution width and Hb% in determining early iron deficiency in pregnant women.Methods: In this study 190 pregnant women were included. CBC including Hb% and RDW and iron profile were done. RDW were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 10 publications
(18 reference statements)
0
22
0
Order By: Relevance
“…However, as according to WHO reports, the dominant type of anemia among pregnant women is iron deficiency [33], this limitation should be relatively minor. As an alternative to measuring serum ferritin, we relied on red cell distribution width, one of the components of the hemogram, as it is considered to be an inflammatory marker and a substitute for serum ferritin in diagnosing iron deficiency anemia [34]. Moreover, our previous studies showed no association between anemia and C-reactive protein [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, as according to WHO reports, the dominant type of anemia among pregnant women is iron deficiency [33], this limitation should be relatively minor. As an alternative to measuring serum ferritin, we relied on red cell distribution width, one of the components of the hemogram, as it is considered to be an inflammatory marker and a substitute for serum ferritin in diagnosing iron deficiency anemia [34]. Moreover, our previous studies showed no association between anemia and C-reactive protein [35].…”
Section: Discussionmentioning
confidence: 99%
“…8 Inflammation inhibits erythropoietin and RBC production as well as reducing the survival of RBCs by damaging RBC memberane and increasing fragility because of increased oxidative stress. 9 Moreover, deficiencies of iron, 10 vitamin B12, 11 and folate 12 are considered as the main factors, which are directly related to the nutritional status. Other clinical conditions, which can increase RDW, are hemolytic anemia and sickle cell anemia are hematological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Since MCHC is a direct assessment of the amount of Hb incorporated into the erythrocytes, MCHC may serve as a reliable and readily accessible indicator of erythrocyte iron load, 11-13,21 that has a high specificity (up to 96%) in detecting iron deficiency. 21 Iron is involved in multiple physiologic functions including oxygen transport (Hb), oxygen storage (myoglobin), oxidative metabolism (mitochondrial oxidative enzymes), 7,22 antioxidant activity (ferritin, myoglobin), and also is involved in the synthesis and degradation of lipids, carbohydrates and nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…21 Iron is involved in multiple physiologic functions including oxygen transport (Hb), oxygen storage (myoglobin), oxidative metabolism (mitochondrial oxidative enzymes), 7,22 antioxidant activity (ferritin, myoglobin), and also is involved in the synthesis and degradation of lipids, carbohydrates and nucleotides. 4,7,22 Traditionally, iron deficiency is only considered important in presence of anemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation